The impact of FDI policies in diversifying the structure of public revenues in the Omani economy for the period 2002-2022 - Salam Kazem Shani (Peerian Journals Publishing, 2025)
The present study investigates how FDI contributes to the diversification of public revenues in the Omani economy between 2002 and 2022. FDI is a key component of the serious economic strategies that many nations have implemented to diversify their sources of public income. The importance of FDI varies by industry, impacting income source diversification and lowering reliance on a single source, hence limiting the possibility of adverse future effects. Using the A.R.D.L model, the study uses sophisticated econometric analysis to quantify how FDI affects public revenues in the oil and gas industry as well as other economic sectors. The study comes to a number of important conclusions, including the following: FDI in the oil and gas extraction industry greatly increases public income in the near term. On the other hand, FDI in other economic sectors has a considerably beneficial influence on public revenues over the long term, while FDI in this area shows a significantly negative effect.
Keywords: FDI; Economic Diversification; Oil and Gas Extraction Sector